1984
DOI: 10.1016/0014-5793(84)80591-8
|View full text |Cite
|
Sign up to set email alerts
|

A phorbol ester and A23187 act synergistically to release acetylcholine from the guinea pig ileum

Abstract: Electrical stimulation of guinea pig ileum preloaded with [3H]choline provokes the release of [3H]acetylcholine (ACh) in a Caz+-dependent manner. This release was markedly increased by the tumor-promoting phorbol ester, 12-O-tetradecanoylphorbol 13-acetate (TPA). The combination of the ionophore A23187 and TPA produced the release of [3H]ACh up to a level equal to or exceeding a maximal response induced by electrical stimulation. A23 187 alone gave only a minor response and TPA alone had no apparent effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…From these results, we suggested an important role of 5-lipoxy genase metabolites in the release of acetylcholine. TPA was reported to increase electrical field stimulation or Ca2+ ionophore-induced acetylcholine release from the myenteric plexus of guinea pig ileum (10). In the present study, PDBu also increased spontaneous and electrical field stimulation-induced acetylcholine release from the same tissue preparations as those in these previous studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…From these results, we suggested an important role of 5-lipoxy genase metabolites in the release of acetylcholine. TPA was reported to increase electrical field stimulation or Ca2+ ionophore-induced acetylcholine release from the myenteric plexus of guinea pig ileum (10). In the present study, PDBu also increased spontaneous and electrical field stimulation-induced acetylcholine release from the same tissue preparations as those in these previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…4(3-Phorbol-12,13-dibutyrate (PDBu) or 12-O-tetra decanoyl phorbol-13-acetate (TPA), an activator of pro tein kinase C, increased acetylcholine release induced by electrical stimulation from rabbit hippocampus in vitro (9) and the release induced by electrical stimulation or a high K+ concentration from the slices of the caudate nucleus of guinea pigs (10). A synaptosome preparation is known to contain high levels of protein kinase C (11) and its substrate proteins (12).…”
mentioning
confidence: 99%
“…One pathway that potentiates presynaptic secretion acts through protein kinase C (PKC, see Tanaka, 1984;Nichols et al,, 1987;Shu and Selmanoff, 1988;Shuntoh et al, 1988; see also Fig. 3).…”
Section: The Impact Of Presynaptic Receptor Activation On the Stimulumentioning
confidence: 99%
“…Takuma and Ichida (32) reported that the combination of A23187 (I /_M) and phorbol 12-myristate 13-acetate (1 ,uM) induced a weak synergistic effect on amylase re lease (about 5%). This synergistic effect is much small er than that seen in other cell types (27)(28)(29)(30)(31). Our pre vious report (33) showed that an increase in DAG accumulation was involved in the potentiating effect of A23187 on carbachol-stimulated amylase release in parotid acinar cells and that this effect was additive.…”
Section: Analysis Of [3h]choline Metabolites Released Into the Mediummentioning
confidence: 69%